Uncovering the constitution's moral design - DeHart, Paul R., 1975- (University of Missouri Press, 2007)
"DeHart examines our constitution's normative framework and moral meaning. He challenges the logical coherency of modern moral philosophy, normative positivism, and other theories that the constitution has been argued to embody and offers groundbreaking methodology that can be applied to uncovering the normative framework of other constitutions as well"--Provided by publisher.